Flexible metal organic framework material with molecular sieving-like performance as well as preparation method and application of flexible metal organic framework material
By preparing a flexible metal-organic framework material [Cu(bpz)(SiF6)], hydrogen bonding was used to enhance acetylene recognition and reduce CO2 binding energy, thus solving the problem of low separation efficiency of acetylene and carbon dioxide and achieving efficient and environmentally friendly separation at room temperature and pressure.
Patent Information
- Application Number
- CN202411581663.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-11-07
AI Technical Summary
Existing acetylene and carbon dioxide separation processes are energy inefficient and environmentally unfriendly, making it difficult to achieve efficient separation of high-purity acetylene at room temperature and pressure.
A flexible metal-organic framework material [Cu(bpz)(SiF6)] was prepared by adding copper hexafluorosilicate solution and 3,5,3,5-tetramethyl-1H,1H-[4,4]bipyrazole solution dropwise under an ice-water environment to form a MOF material with molecular sieving properties. The hydrogen bonding effect was used to enhance acetylene recognition and reduce CO2 binding energy, thereby achieving highly selective separation.
The separation of acetylene/carbon dioxide with high selectivity and high adsorption capacity was achieved at room temperature and pressure. The material is reusable, reducing energy consumption and environmental impact.
Smart Images

Figure CN119285982A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of petrochemical gas separation and purification, and in particular to a flexible metal organic framework material with molecular sieving performance, a preparation method and application thereof. Background Art
[0002] Acetylene is one of the important chemical raw materials. It is the basic raw material of acetaldehyde, acetic acid, benzene, synthetic rubber and synthetic fiber. It usually needs to meet high purity requirements. Therefore, separation and purification is the key process to improve its utilization rate. In industry, acetylene (C2H2) is mainly produced by methane combustion and thermal hydrocarbon cracking. The prepared C2H2 inevitably contains a small amount of CO2 impurities. Therefore, it is of great industrial significance to separate high-purity C2H2 (>99%) from C2H2 / CO2 mixture. Most of the current separation processes use energy-intensive solvent extraction and low-temperature distillation to separate the mixture of acetylene and carbon dioxide. However, due to the close boiling points of the two (acetylene is 189.3K; carbon dioxide is 194.7K), the separation is extremely difficult. The energy efficiency of these methods is low and they are very unfriendly to the environment. Therefore, it is necessary to develop new separation technologies at room temperature and pressure to efficiently separate acetylene and carbon dioxide.
[0003] In recent years, the use of adsorbent separation technology for gas separation and purification has attracted great attention from academia and industry. This makes it possible for future separation technology to shift from traditional energy-intensive cryogenic distillation to energy-saving adsorbent separation. Adsorption separation, as an energy-saving and efficient separation technology, has the characteristics of low energy consumption and simple operation, and can also achieve higher separation selectivity. With the development of adsorption separation materials such as carbon materials, molecular sieves, and porous polymers, adsorption separation technology has made great progress in the field of gas separation.
[0004] Metal-organic framework materials are a type of crystalline porous materials with a certain composition and structure formed by self-assembly of metal nodes and organic ligands. Due to its adjustable pore size, high specific surface area, and easy functionalization, it has developed rapidly and has become a highly promising adsorbent material in the field of low-carbon hydrocarbon gas separation and purification.
[0005] When metal-organic framework materials are used in gas separation and purification, high adsorption capacity and high selectivity are often a difficult and challenging task to balance. The anion-pillared SIFSIX series of materials have one-dimensional regular linear channels, which can effectively aggregate the target gas during the adsorption process. By replacing the metal ion center or selecting organic linkers with specific functional elements, the skeleton can form hydrogen bonds, coordination bonds or van der Waals forces with the target gas molecules, effectively improving the skeleton's ability to recognize the target gas. Therefore, the SIFSIX series of materials are expected to solve the trade-off effect that has not yet been solved in ordinary metal-organic framework materials. Summary of the invention
[0006] In order to overcome the shortcomings of traditional C2H2 / CO2 separation, the present invention provides a flexible metal-organic framework material with molecular sieving properties and a preparation method and application thereof. The flexible metal-organic framework material of the present invention has a large adsorption capacity for acetylene at room temperature and pressure and extremely high selectivity for C2H2 / CO2 separation.
[0007] To achieve the above object, the present invention adopts the following technical solution:
[0008] A method for preparing a flexible metal-organic framework material with molecular sieving-like properties comprises the following steps: dripping a copper hexafluorosilicate solution dropwise into a 3,5,3,5-tetramethyl-1H,1H-[4,4]bipyrazole solution in an ice-water environment; after the dripping is completed, stirring the reaction in an ice-water environment for 10-15 hours; and post-treating the resulting reaction solution to obtain the flexible metal-organic framework material [Cu(bpz)(SiF6)] with molecular sieving-like properties, thereby completing the preparation.
[0009] Furthermore, the molar ratio of the 3,5,3,5-tetramethyl-1H,1H-[4,4]bipyrazole to copper hexafluorosilicate is 1.5-2.5:1, preferably 2-2.5:1.
[0010] Furthermore, the solvent of the 3,5,3,5-tetramethyl-1H,1H-[4,4]bipyrazole solution is methanol, and the volume of the solvent is 10-15 L / mol, preferably 13.5-14 L / mol, based on the amount of 3,5,3,5-tetramethyl-1H,1H-[4,4]bipyrazole.
[0011] Furthermore, the solvent of the copper hexafluorosilicate solution is water, and the volume of the solvent is 20-40 L / mol, preferably 28-32 L / mol, based on the amount of copper hexafluorosilicate.
[0012] Furthermore, the dripping speed of the copper hexafluorosilicate solution is 0.01-0.15 mL / s.
[0013] Specifically, the present invention recommends that both solutions be precooled at 0°C before the copper hexafluorosilicate solution is added dropwise to the 3,5,3,5-tetramethyl-1H,1H-[4,4]bipyrazole solution. Generally, 50-60 minutes are sufficient. In an embodiment of the present invention, the precooling time is 50 minutes. The present invention also recommends that the copper hexafluorosilicate solution be continuously stirred during the addition process to prevent it from settling before the addition.
[0014] Furthermore, the reaction temperature is 0°C.
[0015] Furthermore, the post-treatment is as follows: filtering the reaction solution, washing the obtained filter cake with anhydrous methanol for several times, and drying to obtain the metal organic framework material [Cu(bpz)(SiF6)].
[0016] The present invention also provides the application of the flexible metal organic framework material with molecular sieving-like performance in the adsorption and separation of C2H2 / CO2 in mixed gases.
[0017] The metal salt prepared by the flexible metal organic framework material of the present invention is copper hexafluorosilicate, and the organic ligand is 3,5,3,5-tetramethyl-1H,1H-[4,4]bipyrazole. Due to the suitable pore size and fluorinated functional sites, the material enhances the recognition of acetylene through the strong hydrogen bond interaction formed between the anion column and the pyrazole ligand and C2H2. However, due to the presence of methyl groups, the binding energy of the material to CO2 is reduced, so the CO2 molecules cannot open the framework pores, and the macroscopic effect of basically no adsorption is produced, thereby having a molecular sieve-like screening effect. The huge adsorption difference of the framework material to C2H2 and CO2 can be used to separate C2H2 / CO2 mixed gases, and the separation selectivity is extremely high and the adsorption capacity of C2H2 is large. It is a relatively excellent solid physical adsorbent with both characteristics.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] (1) The metal-organic framework material of the present invention is based on the inorganic metal ion Cu 2+ 、Inorganic anion SiF6 2-The ultra-microporous metal-organic framework material [Cu(bpz)(SiF6)] is obtained by stirring with an organic ligand 3,5,3,5-tetramethyl-1H,1H-[4,4]bipyrazole in an ice-water environment. The metal-organic framework material of the present invention can enhance the capture of acetylene through the interaction of hydrogen bonds, and because the presence of methyl groups reduces the binding energy of the material to CO2, CO2 molecules cannot open the pores of the flexible skeleton, resulting in the extremely low adsorption of carbon dioxide by the metal-organic framework material, which can be ignored and has a molecular sieving effect. The rotation of the methyl groups on the pyrazole ring causes the opening and closing of the pore windows, making the material completely flexible.
[0020] (2) The flexible metal organic framework material with molecular sieving properties of the present invention can be used to separate C2H2 / CO2 mixed gas due to its huge adsorption difference for C2H2 and CO2, and basically does not absorb CO2, and has molecular sieving properties. The material can be reused after multiple desorption / adsorption, showing great potential in industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is the XRD spectrum of the flexible MOF material with molecular sieving-like properties prepared in Example 1.
[0022] Figure 2 These are the nitrogen adsorption-desorption isotherms and the CO2 adsorption isotherms of the flexible MOF material with molecular sieving-like properties prepared in Example 1.
[0023] Figure 3 This is a C2H2 / CO2 adsorption curve of the flexible MOF material with molecular sieving-like properties prepared in Example 1.
[0024] Figure 4 This is the IAST selectivity diagram of the MOF material with molecular sieving-like properties prepared in Example 1 for C2H2 / CO2 mixed gas at 296K.
[0025] Figure 5 This is the Qst curve of Example 1 for C2H2 gas at 296K. DETAILED DESCRIPTION
[0026] The technical solution of the present invention is further described in detail below through specific embodiments in conjunction with the accompanying drawings.
[0027] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments, unless otherwise specified, are conventional methods in the art.
[0028] Example 1
[0029] 0.29mmol of 3,5,3,5-tetramethyl-1H,1H-[4,4]bipyrazole was dispersed in 4mL of methanol by shaking, which was recorded as solution A; 0.13mmol of copper hexafluorosilicate was dissolved in 4mL of deionized water, which was recorded as solution B. Solutions A and B were precooled in an ice-water mixture for 50min at the same time. Solution B was slowly added dropwise to solution A while stirring at 0℃, and the drop rate was kept between 0.01-0.15mL / s. The mixed solution was stirred in an ice-water environment at 0℃ for 12h. After the reaction, a blue-purple powder was obtained by filtering, which was rinsed three times with anhydrous methanol and dried in vacuum at 50℃ to obtain a new flexible MOF material with molecular sieving properties.
[0030] The purity of the flexible MOF material prepared in Example 1 was first verified by powder X-ray diffraction. The XRD pattern of the flexible MOF material is as follows: Figure 1 As shown, it can be seen that the XRD characterization results of the flexible MOF material are consistent with the simulation.
[0031] The fitting XRD pattern of MOF material is obtained as follows:
[0032] 1) Cultivate single crystal: drip the lower solution, transition layer solution and upper solution into the test tube in sequence. The lower solution is an ethylene glycol solution (1 mL) containing 0.005 g of copper hexafluorosilicate, the transition layer solution is a methanol / ethylene glycol mixed solution (0.75 mL each of methanol and ethylene glycol) with a volume ratio of 1:1, and the upper solution is a methanol solution (1 mL) containing 0.0058 g of 3,5,3,5-tetramethyl-1H,1H-[4,4]bipyrazole. Then place the test tube in a constant temperature incubator at 27°C and let it stand for 3 months to obtain blue-purple crystals, that is, single crystals;
[0033] 2) Fitting XRD pattern of MOF material: The single crystal obtained in step 1) is subjected to XRD analysis to obtain a fitting XRD result.
[0034] Then, the specific surface area of the flexible MOF material prepared in Example 1 was characterized by using the N2 adsorption-desorption isotherm at 77K. However, even under low temperature conditions, N2 was still blocked outside the pores, resulting in almost no N2 adsorption at 77K. Therefore, the characterization gas was replaced and the specific surface area of [Cu(bpz)(SiF6)] was characterized by the CO2 adsorption-desorption isotherm at 195K, as shown in FIG. Figure 2 As shown in Figure 2, under the conditions of 195K and 1 bar, the material's adsorption capacity for CO2 is 116.12 (cm 3 / g STP), the curve is a type I adsorption isotherm, showing the characteristics of microporous materials, and the calculated BET specific surface area is 180.237m 2 / g.
[0035] pass Figure 1 and Figure 2 As a result, it can be seen that the flexible MOF material synthesized in Example 1 is [Cu(bpz)(SiF6)].
[0036] The gas separation ability of the flexible MOF material in Example 1 was tested. Before the gas adsorption separation ability test, the guest solvent in the skeleton was removed by activation treatment: first, the newly synthesized flexible MOF material product powder sample with molecular sieving-like properties was subjected to at least 8 solvent exchanges with dry methanol in one day, and then the temperature was raised to 50°C on a Micromeritics ASAP 2020 instrument at a heating rate of 1°C / min and vacuumed for 24 hours until the exhaust rate was 4 mm Hg / min before measurement.
[0037] The gases used for gas separation capability testing are C2H2 and CO2, the temperature is 296K, and can be stabilized by a low-temperature thermostatic bath. The test pressure is 0-1 bar. The gases used and their purity include: N2 (>99.999%), He (99.999%), C2H2 (99.99%), CO2 (99.99%), and the dry methanol used for exchange is HPLC grade methanol produced by AlfaAesar.
[0038] The gas adsorption test was carried out using Micromeritics ASAP 2020 fully automatic adsorption instrument, and the adsorption isotherm obtained is as follows: Figure 3 As shown in Figure 2, it can be seen that at 296K and 1 bar, the adsorption capacity of acetylene is as high as 92.1 cm 3 / g, adsorption capacity of carbon dioxide 2cm 3 / g.
[0039] The pure component isotherm data of C2H2 and CO2 at 296K were fitted and calculated in origin according to the two-site Langmuir-Freundrick isotherm model. The results are shown in Figure 4 As shown. According to IAST calculation, at 296K and 1 bar, the IAST selectivity of C2H2 / CO2 (50 / 50, v / v) is about 1*10 5 It can be seen that this new type of MOF material with molecular sieving properties has excellent gas adsorption capacity and extremely excellent separation selectivity.
[0040] In order to further explore the magnitude of the interaction force between metal organic framework materials and C2H2 and CO2 gas molecules, the isosteric adsorption heat (Q st ) to explain, such as Figure 5As shown in the figure, since the MOF material basically does not adsorb CO2, the corresponding adsorption heat is not calculated. As can be seen from the figure, Q st The value is 40.5KJ / mol. With the increase of acetylene loading, Q st The value decreased slightly, which may be due to the fact that acetylene molecules entered the framework and occupied the adsorption sites, resulting in a decrease in the number of active sites.
[0041] Example 2
[0042] Example 2 Preparation of Flexible MOF Material Example 1 was repeated, except that the reaction temperature was replaced with room temperature, i.e. the mixed solution was stirred at room temperature for 12 h. The other conditions remained unchanged, and a flexible MOF material was finally obtained. The MOF material prepared in Example 2 was characterized by XRD, and its XRD curve was consistent with the simulation. However, at 296 K and 1 bar, the adsorption capacity of acetylene was only 24 cm 3 / g.
[0043] The adsorption performance of the flexible MOF material in Example 2 is not ideal. The reason is that the coordination between copper ions and organic ligands will be reduced at room temperature, thus affecting the material performance.
[0044] Example 3 (the ratio of the reaction ligand to the salt is different from that of Example 1)
[0045] Example 3 Preparation of Flexible MOF Material Example 1 was repeated, except that the amount of copper hexafluorosilicate was replaced with 0.29 mmol, and the other conditions remained unchanged, and a flexible MOF material was finally obtained. The MOF material prepared in Example 3 was characterized by XRD, and its XRD curve showed a large number of impurity peaks at around 20°, indicating that the flexible MOF material in Example 3 was impure, which may be due to the incomplete reaction of the ligand with the salt.
[0046] Comparative Example 1
[0047] Comparative Example 1 Preparation of Flexible MOF Materials Example 1 was repeated, with the only difference being that "0.13 mmol copper hexafluorosilicate was dissolved in 4 mL of deionized water, recorded as solution B, instead of dissolving 0.13 mmol copper hexafluorosilicate in 4 mL of N,N-dimethylformamide, recorded as solution B", and the other conditions remained unchanged. Finally, a blue-purple product was obtained by filtration and drying. XRD testing showed that the desired material was not synthesized. The possible reason may be that copper ions cannot coordinate with ligands in the environment of DMF and methanol.
[0048] Comparative Example 2
[0049] Disperse and dissolve 0.29mmol of 3,5,3,5-tetramethyl-1H,1H-[4,4]bipyrazole in 4mL of methanol, which is called solution A; dissolve 0.13mmol of copper hexafluorozirconate in 4mL of deionized water, which is called solution B. Precool solutions A and B in an ice-water mixture for 50min. Add solution B dropwise to solution A while stirring at 0℃, and keep the drop rate between 0.01-0.15mL / s. Stir the mixed solution in an ice-water environment at 0℃ for 12h. After the reaction, filter to obtain a solid product, rinse it three times with anhydrous methanol, and dry it in vacuum at 50℃ to obtain the product.
[0050] The product of Comparative Example 2 was characterized by XRD and found to have impurity peaks. This is because the atomic radius of zirconium is much larger than that of silicon atoms and cannot coordinate to form MOF.
[0051] Comparative Example 3
[0052] 0.29 mmol of 3,5,3,5-tetramethyl-1H,1H-[4,4]bipyrazole was dispersed in 4 mL of chloroform, and 0.13 mmol of copper hexafluorosilicate was dissolved in 2 mL of deionized water. The two were mixed, and the mixed solution was heated to reflux at 50°C for 12 hours. The mixed solution was filtered, washed, dried, and characterized. The product was characterized by XRD and showed that there were many impurity peaks and the purity was insufficient. The possible reason was that the ligand could not coordinate well with the copper ion in the chloroform and water system.
[0053] Comparative Example 4
[0054] Comparative Example 4 Preparation of Flexible MOF Material Example 1 was repeated, with the only difference being that "copper hexafluorosilicate was replaced with an equal molar amount of zinc hexafluorosilicate", and other conditions remained unchanged, and finally a MOF material was obtained.
[0055] The XRD curve of the MOF material in Comparative Example 4 is consistent with the simulation, but the adsorption of acetylene is too low at 296K and 1 bar, which is 37 cm 3 / g. The reason may be that the radius of zinc atoms is larger than that of copper atoms, so the pores of the MOF materials are larger, but the hydrogen bonding force is reduced, so the absorbed acetylene is greatly reduced.
[0056] Comparative Example 5
[0057] Comparative Example 5 Preparation of Flexible MOF Material Example 1 was repeated, with the only difference being that "3,5,3,5-tetramethyl-1H,1H-[4,4]bipyrazole ligand was replaced with an equal molar amount of tetraethylbipyrazole (92494-09-2)", and the other conditions remained unchanged, and finally a MOF material was obtained.
[0058] The XRD curve of the MOF material in Comparative Example 5 is consistent with the simulation, but the adsorption of acetylene is too low at 296K and 1 bar, which is 12 cm3 / g, the reason may be that the structure of tetraethyl bipyrazole ligand is too long, and the prepared MOF material is not conducive to the formation of a certain adsorption channel.
[0059] Comparative Example 6
[0060] Comparative Example 6 Preparation of Flexible MOF Material Repeat Example 1, the only difference is that "3,5,3,5-tetramethyl-1H,1H-[4,4]bipyrazole ligand is replaced by an equal molar amount of bipyrazole (16227-15-9)", and other conditions remain unchanged, and finally the MOF material is obtained.
[0061] XRD characterization of the MOF material product in Comparative Example 6 showed that there were many impurity peaks and the purity was insufficient. It was considered that Cu and the ligand were not properly matched.
[0062] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a flexible metal organic framework material with molecular sieving properties, characterized in that The following steps are involved: The copper hexafluorosilicate solution is added drop by drop into the 3,5,3,5-tetramethyl-1H,1H-[4,4]bipyrazole solution in an ice-water environment. After the addition is completed, the reaction is stirred in an ice-water environment for 10-15 hours. The resulting reaction solution is post-treated to obtain the flexible metal organic framework material [Cu(bpz) (SiF6)] with molecular sieving-like properties. The preparation is completed.
2. A method for preparing a flexible metal organic framework material with molecular sieving properties as claimed in claim 1, characterized in that The molar ratio of the 3,5,3,5-tetramethyl-1H,1H-[4,4]bipyrazole to copper hexafluorosilicate is 1.5-2.5:1, preferably 2-2.5:
1.
3. The method for preparing a flexible metal organic framework material having molecular sieving properties as claimed in claim 1, characterized in that The solvent of the 3,5,3,5-tetramethyl-1H,1H-[4,4]bipyrazole solution is methanol, and the volume of the solvent is 10-15 L / mol based on the amount of 3,5,3,5-tetramethyl-1H,1H-[4,4]bipyrazole.
4. A method for preparing a flexible metal organic framework material with molecular sieving properties as claimed in claim 1, characterized in that The solvent of the copper hexafluorosilicate solution is water, and the volume of the solvent is 20-40 L / mol based on the amount of copper hexafluorosilicate.
5. The method for preparing a flexible metal organic framework material having molecular sieving-like properties according to claim 1, characterized in that The dripping speed of the copper hexafluorosilicate solution is 0.01-0.15 mL / s.
6. The method for preparing a flexible metal organic framework material with molecular sieving-like properties according to claim 1, characterized in that: The reaction temperature is 0°C.
7. The method for preparing a flexible metal organic framework material having molecular sieving-like properties according to claim 1, characterized in that The post-treatment is as follows: filtering the reaction solution, washing the obtained filter cake with anhydrous methanol for several times, and drying to obtain the metal organic framework material [Cu (bpz) (SiF6)].
8. A flexible metal organic framework material having molecular sieving-like properties prepared by the method according to any one of claims 1 to 7.
9. Use of the flexible metal organic framework material with molecular sieving-like properties as claimed in claim 8 in the adsorption and separation of C2H2 / CO2 in mixed gases.
Citation Information
Patent Citations
Metal organic framework material as well as preparation method and application thereof
CN114573829A
Fluorosilicate MOF (Metal Organic Framework) material as well as preparation method and application thereof
CN115678024A
Ion hybridization grade hole metal organic framework material with wly topological structure as well as preparation and application of ion hybridization grade hole metal organic framework material
CN116554492A
Green methods for preparing highly co2 selective and h2s tolerant metal organic frameworks
US20170137450A1
Process for preparing metal organic frameworks having improved water stability
US20210268476A1